2013
DOI: 10.1155/2013/892974
|View full text |Cite
|
Sign up to set email alerts
|

Sedation of Newborn Infants for the INSURE Procedure, Are We Sure?

Abstract: Background. Neonatal intubation is a stressful procedure that requires premedication to improve intubation conditions and reduce stress and adverse physiological responses. Premedication used during the INSURE (INtubation, SURfactant therapy, Extubation) procedure should have a very short duration of action with restoration of spontaneous breathing within a few minutes. Aims. To determine the best sedative for intubation during the INSURE procedure by systematic review of the literature. Methods. We reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…A recent review on the use of premedication before intubation during the INSURE procedure showed no conclusive evidence on the optimal premedication but stated that remifentanil was probably the best candidate because of its unique pharmacological profile [4]. Remifentanil has an extremely brief action, high predictability, rapid onset and offset of action, and immediate recovery of the clinical effect after interruption of the administration [5].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review on the use of premedication before intubation during the INSURE procedure showed no conclusive evidence on the optimal premedication but stated that remifentanil was probably the best candidate because of its unique pharmacological profile [4]. Remifentanil has an extremely brief action, high predictability, rapid onset and offset of action, and immediate recovery of the clinical effect after interruption of the administration [5].…”
Section: Introductionmentioning
confidence: 99%
“…Administering atropine and ketamine before LISA resulted in low pain scores and stable haemodynamic parameters, but relatively frequent adverse respiratory events. and strongly recommended for the intubation surfactant extubation procedure (9). Surprisingly, most studies on the LISA procedure did not include analgosedation (7), although awake laryngoscopy is known to be painful and associated with adverse events (10,11).…”
Section: Key Notesmentioning
confidence: 99%
“…Uncertainties about the feasibility and the nature of administering premedication before this procedure are potential barriers to its wider implementation . Premedication is currently considered mandatory for all nonemergent neonatal intubations and strongly recommended for the intubation surfactant extubation procedure . Surprisingly, most studies on the LISA procedure did not include analgosedation , although awake laryngoscopy is known to be painful and associated with adverse events .…”
Section: Introductionmentioning
confidence: 99%
“…This implies that neonates in the first week of postnatal life are at an increased risk for accumulation during either intermittent bolus or continuous administration of propofol, irrespective of the age or weight at birth . This PK knowledge was subsequently integrated in a propofol dose‐finding study (effective dose for 50% of patients, ED 50 ) through 8 patient strata (postmenstrual and postnatal age) to attain optimal effects for endotracheal intubation in neonates for the INSURE (intubation, surfactant administration, extubation) indication . It was determined that the ED 50 dose for preterm neonates varied between 0.7 and 1.4 mg/kg.…”
Section: Dose Determination Of Common Analgosedative Drugsmentioning
confidence: 99%
“…50 This PK knowledge was subsequently integrated in a propofol dose-finding study (effective dose for 50% of patients, ED 50 ) through 8 patient strata (postmenstrual and postnatal age) to attain optimal effects for endotracheal intubation in neonates for the INSURE (intubation, surfactant administration, extubation) indication. 51,52 It was determined that the ED 50 dose for preterm neonates varied between 0.7 and 1.4 mg/kg. This is significantly lower than initially suggested in literature.…”
Section: Sedativesmentioning
confidence: 99%